1989
DOI: 10.1073/pnas.86.19.7606
|View full text |Cite
|
Sign up to set email alerts
|

Interleukin 1 regulates synthesis of amyloid beta-protein precursor mRNA in human endothelial cells.

Abstract: We have analyzed the modulation of amyloid (3-protein precursor (APP) gene expression in human umbilical vein endothelial cells (HUVEC). The level of the APP mRNA transcripts increased as HUVEC reached confluency. In confluent culture the half-life of the APP mRNA was 4 hr. Treatment of the cells with human recombinant interleukin 1 (IL-1), phorbol 12-myristate 13-acetate, or heparin-binding growth factor 1 enhanced the expression of APP gene in these cells, but calcium ionophore A23187 and dexamethasone did n… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

3
237
2
9

Year Published

1994
1994
2003
2003

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 510 publications
(254 citation statements)
references
References 49 publications
3
237
2
9
Order By: Relevance
“…AP-1 has been proposed as a master switch for the expression of several genes. Postischemic increase in AP-1 binding activity may underline one of the molecular mechanisms allowing the surviving neurons to adapt to the degenerative processes after ischemic brain injury [65][66][67]. In summary, our studies demonstrate the feasibility of an in vivo antisense strategy to suppress the postischemic expression of an immediate early gene.…”
mentioning
confidence: 57%
“…AP-1 has been proposed as a master switch for the expression of several genes. Postischemic increase in AP-1 binding activity may underline one of the molecular mechanisms allowing the surviving neurons to adapt to the degenerative processes after ischemic brain injury [65][66][67]. In summary, our studies demonstrate the feasibility of an in vivo antisense strategy to suppress the postischemic expression of an immediate early gene.…”
mentioning
confidence: 57%
“…Likewise, recent studies have also suggested that Cu 2ϩ chelation may represent an alternative approach to the management of ␤-amyloid deposition in a transgenic mouse model of Alzheimer's disease. Because IL-1␣ expression is enhanced significantly in the brains of Alzheimer's disease patients (50) and is able to induce the expression of the ␤-amyloid precursor gene in human endothelial cells in vitro (51), the therapeutic effect of Cu 2ϩ chelators in Alzheimer's pathology may be due to their ability to inhibit the release of IL-1␣.…”
Section: Discussionmentioning
confidence: 99%
“…In addition, post-mitotic neurons which overexpress full-length APP were shown to degenerate and accumulate large amounts of amyloidogenic C-terminal fragments (9). The promoter region of the APP gene (10) has been shown to contain binding sequences for several known transcription factors (11)(12)(13)(14)(15)(16)(17)(18)(19). We reported recently (20) that a novel regulatory pathway for APP gene control at the transcriptional level may involve members of the NF-B/Rel family.…”
mentioning
confidence: 99%
“…In fact IL-1 is induced in the central nervous system following a variety of insults (23). Moreover, the cytokine is dramatically overexpressed in brains of individuals with AD and Down's syndrome (24) and it induces an increase in APP transcript levels in endothelial (11) and neuronal cells (25). On the other hand, the role of glutamate as a mediator of acute neurodegenerative events is well recognized (26).…”
mentioning
confidence: 99%